2014
DOI: 10.1002/2013jb010478
|View full text |Cite
|
Sign up to set email alerts
|

Temporal variability and tidal modulation of hydrothermal exit‐fluid temperatures at the Lucky Strike deep‐sea vent field, Mid‐Atlantic Ridge

Abstract: We deployed autonomous temperature sensors at black smoker chimneys, cracks, and diffuse flow areas at the Lucky Strike hydrothermal field (Mid-Atlantic Ridge,~37°17'N) between summer 2009 and summer 2012 and contemporaneously measured tidal pressures and currents as part of the long-term MoMAR experiment to monitor hydrothermal activity. We classify the temperature data according to the hydrogeologic setting of the measurement sites: a high-temperature regime (>190°C) representing discharge of essentially unm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
93
2

Year Published

2016
2016
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 115 publications
(99 citation statements)
references
References 56 publications
4
93
2
Order By: Relevance
“…For the NEP, the tidal influence appeared to wane in high-temperature records, making tidal signals less clear or even non-existent (Tivey et al, 2002;Hautala et al, 2012). While for the MAR the semi-diurnal variability in the hightemperature records was shown to be more significant and to be more coherent with pressure than those observed in lowtemperature records (Barreyre et al, 2014). Unfortunately, we cannot corroborate this with the current study as only low-temperature time series were recorded by both ecological observatories.…”
Section: Long-term Environmental Variations and Rhythmscontrasting
confidence: 70%
See 1 more Smart Citation
“…For the NEP, the tidal influence appeared to wane in high-temperature records, making tidal signals less clear or even non-existent (Tivey et al, 2002;Hautala et al, 2012). While for the MAR the semi-diurnal variability in the hightemperature records was shown to be more significant and to be more coherent with pressure than those observed in lowtemperature records (Barreyre et al, 2014). Unfortunately, we cannot corroborate this with the current study as only low-temperature time series were recorded by both ecological observatories.…”
Section: Long-term Environmental Variations and Rhythmscontrasting
confidence: 70%
“…Several studies reveal the presence of tidal cycles in environmental variables (such as currents, fluid emission, temperature) in the deep sea, particularly in hydrothermal vents (e.g. Tivey et al, 2002;Thomsen et al, 2012;Barreyre et al, 2014;Sarrazin et al, 2014;Lelièvre et al, 2017) and the influence of tides on the deepsea organisms has been previously inferred. Additionally, an actual tidal rhythm has been revealed in visible faunal densities and appearance rate for inhabitants of various deepsea chemosynthetic environments -e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past several decades, a large number of studies have observed episodic and periodic variations in long-term monitoring of venting temperature, flow rate, and chemical compositions at both low-and high-temperature hydrothermal systems over a broad range of time scales [e.g., Little et al, 1988;Schultz et al, 1996;Sohn et al, 1998;Tivey et al, 2002;Scheirer et al, 2006;Larson et al, 2007Larson et al, , 2009Nees et al, 2009;Crone et al, 2010;Barreyre et al, 2014b]. In particular, spectral analysis has identified strong tidal signatures in hydrothermal venting in many of these studies.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, other studies interpret observed tidal oscillations, especially in measurements of hightemperature venting made inside the vent chimney, as the poroelastic response of crustal fluids to seafloor tidal loading [e.g., Larson et al, 2007Larson et al, , 2009; Barreyre et al, 2014b;Barreyre and Sohn, 2016]. Based on observations made at the Lucky Strike Hydrothermal Field on the Mid-Atlantic Ridge, Barreyre et al [2014b] suggested that low-temperature venting (i.e., diffuse flows) is mostly affected by bottom currents while hightemperature venting (i.e., ''black smokers'') is mostly affected by tidal loading.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation